KONSUMSI DAN KECERNAAN BAHAN KERING PAKAN SAPI BALI JANTAN YANG DISUPLEMENTASI COMPLETE RUMEN MODIFIER - Zalzabila, Nida Maulidia; Suhartati, Fransisca Maria; Bata, Muhamad (ANGON: Journal of Animal Science and Technology, 2024)
The purpose of this study was to examine the effect of Complete Rumen Modifier (CRM) administration on dry matter consumption and digestibility of male Bali cattle feed and to provide a solution to prevent acidosis in cattle. The material used was 3 male Bali cattle aged 24 months with an average body weight of 209 kg. The research design used RBSL 3x3, the treatments tested were P1 (rice straw + 2% concentrate of body weight), P2 (P1 + CRM 0.5% from DM concentrate), and P3 (P1 + CRM 1% from DM concentrate). The variables measured were consumption and digestibility of dry matter (BK), the data obtained was tested using analysis of variance and the Orthogonal Polynomial test. The results of the analysis of variance showed that the treated feed had a significant effect (P<0.05) on consumption and dry matter digestibility (BK). The Orthogonal Polynomial test shows that the higher the administration of CRM up to 1% level, the consumption and digestibility of dry matter increases linearly respectively with the equation y = 4,41x + 63,10 with r2=0,50 dan y = 5,79x + 70,43 with r2=0,84. The conclusion obtained is that the provision of concentrate feed with the addition of CRM up to 1% level can increase consumption and digestibility of BK.